Performance of concrete paving blocks reinforced with bamboo and rice husk ash as partial replacement for cement (2013)
This research involved the production and evaluation of concrete paving blocks (CPBs) by partially replacing the cement content by rice husk ash (RHA) and addition of bamboos. One of the problems usually experienced during the service life of concrete paving blocks include occasional failure due to excessive surface wear. This has led to the preference of other materials of construction. CPB samples with 100% cement content plus 0%, 1%, 2%, and 3% bamboo by weight of cement were produced. Others were 0%, 10%, 20%, and 30% cement replacement with RHA plus 3% in each were produced. Mechanical tests including compressive, flexural and abrasive strength tests were performed on the samples and the results gotten were analyzed. It was observed that cement replacement up to 20% by RHA with 3% is appropriate in strength. Also, the presence of in the blocks had a positive effect on their strength properties. Surface wear in all the CPB samples were also observed to have drastically reduced far below the 1% allowable limit.